Perancangan Tempat Tidur Multifungsi untuk Anak - Meliana, Fenny (Intra, 2015)
At the beginning of childâs birth, the most needed furniture is the baby crib, considering the babyâs main activity is also sleeping for almost 20 hours a day. The presence of baby crib isnât just tofacilitate the babyâs sleeping activity, but also to support the safety level of the baby when theyâre asleep. Along with the development of age , the body and also the development of the childs activity, the needs of furniture is increasing as well, corresponding with the activity done by the child.Â  Not just the crib, but also some other furniture too. This design is done in order to create an innovation of childâs crib furniture. The field survey results and some design ideas show that a baby crib can be developed furthermore if reviewed in terms of the value of the function and usage period contained within the object. By using several steps of method, such as data collection, data processing, data analysis, and the design itself, it is expected to reach a brand-new design of simple multifunctional furniture for children that can meet the requirements in accordance with the activity and development of the children that is easy to applied and can be adjusted to the needs.